The Value of Cryosurgery in Treating a Case of Thoracic Chondrosarcoma. (10th May 2011) - Alpantaki, Kalliopi; Datsis, George; Zoras, Odysseas; Kampouroglou, Alkisti; Drositis, Ioannis; Halkiadakis, George; Katonis, Pavlos
Abstract : Chondrosarcomas of the spine are rare and difficult to treat. In this paper a case of thoracic chondrosarcoma is presented. Chondrosarcomas of the spine are generally smaller, more difficult to excise and are followed by higher local recurrence compared with chondrosarcomas of the peripheral skeleton. The tumor is radio- and chemoresistant, making the surgical treatment of utmost importance. The most important prognostic factor for local control is wide or marginal tumor resection. Our patient was treated in two stages, with total excision of the tumor, using cryosurgery. Liquid nitrogen was used to freeze the damaged tissue at a cellular level and made the excision more efficient.